PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN SELF EFFICACY TERHADAP MOTIVASI GURU SEKOLAH DASAR NEGERI DI KECAMATAN KRAMAT JATI, JAKARTA TIMUR - Dwi Endah Wahyuningsih (Universitas Negeri Jakarta, 2015)
The purpose of this research is to determine the effect of transformational leadership and self-efficacy on motivation the teacher state primary school the district of Kramat Jati East Jakarta. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) transformasional leadership has a positive direct effect in motivation, (2) self-efficacy has a positive direct effect in motivation, (3) transformational leadeship has a positive direct effect in self-efficacy.